Gonadotropin-Releasing Hormone Agonist Use to Guide Diagnosis and Treatment of Autoimmune Progesterone Dermatitis. Issue 5 (May 2015) - Domeyer-Klenske, Amy; Robillard, Diana; Pulvino, John; Spratt, Daniel
Abstract : BACKGROUND: Autoimmune progesterone dermatitis is a catamenial disorder traditionally diagnosed by subcutaneous or intramuscular progesterone challenge. Little has been reported regarding the use of a gonadotropin-releasing hormone (GnRH) agonist with a progestin add-back challenge to diagnose and guide management of this condition. CASE: A 50-year-old premenopausal woman presented with cyclic facial rash minimally responsive to standard treatment. Symptoms improved with depot leuprolide acetate and worsened with add-back progesterone therapy. Hysterectomy and oophorectomy were performed with resolution of symptoms. This surgery eliminated endogenous progesterone and permitted estrogen replacement to treat vasomotor symptoms experienced with GnRH agonist therapy. CONCLUSION: This case of autoimmune progesterone dermatitis exemplifies the utility of GnRH agonists with a steroid add-back challenge for diagnosing catamenial disorders and guiding treatment. Abstract : Gonadotropin-releasing hormone agonists with steroid add-back therapy can be used by gynecologists to guide diagnosis and treatment of catamenial disorders such as autoimmune progesterone dermatitis.